Design and experimental investigation of a novel thermal energy storage unit with phase change material. (November 2021) - Zhang, Tingwei; Lu, Gaofeng; Zhai, Xiaoqiang
Abstract: A novel design of a shell-and-tube thermal energy storage unit with phase change material was proposed in the study. The layouts of highly conductive fins and phase change material (PCM) in the energy storage unit were optimized through the topology optimization method. The optimal choice of volume ratio of fins was recommended as 20% considering the fin configuration, the heat transfer performance and energy storage capacity. For the convenience of fabrication, the topology-optimized fin configuration was extracted and reconstructed by the threshold screening of design variables and contour filling method. Taking conventional longitudinal fins as a comparison, the experimental results indicated that the newly designed fins could significantly reduce the whole phase transition time for both charging and discharging processes, enhancing the heat transfer process in the energy storage unit over 40%. This new fin configuration is recommended for efficient use in practical thermal energy storage systems for energy saving. Highlights: A novel design of highly conductive fins in thermal energy storage unit with phase change material is proposed. Superior heat transfer performance is obtained by the topology optimization method. Heat transfer enhancement of topology optimization is verified by the experimental investigation.